The Effect of Profitability, Leverage, and Managerial Ownership on Earnings Management - Margaretha Putri Prasetyo; Rousilita Suhendah (International Journal of Application on Economics and Business, 2023)
This study aims to determine the effect of profitability, leverage, and managerial ownership on earnings management in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. This study used 30 manufacturing companies as a sample with the purposive sampling method. In this research, Microsoft Excel and EViews 12 was used to assist in data processing. The results of this study show that profitability has positive and significant effect on earnings management, leverage and managerial ownership has no effect on earnings management. This research can be useful for company management, investors, and creditors in dealing with factors that affect earnings management.